Community real estate development : a history and how-to for practitioners, academics, and students - Buckman, Stephen (New York, NY : Routledge, 2022)
"Community Real Estate Development: A History and How-To for Practitioners, Academics, and Students introduces the fundamentals of affordable housing to aspiring development professionals. From understanding the history informing today's affordable housing programs to securing financing and partnering with public and private stakeholders, this primer equips students and emerging professionals for success in a unique area of the real estate industry"--
OCLC-licensed vendor bibliographic record.
Keywords: Real estate development; Real estate business; Housing; Community development -- History; BUSINESS & ECONOMICS / Real Estate; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Development / General